Model penerapan etika pelayanan pekerja wanita spa pada hotel berbintang di desa adat seminyak - Kesumadewi, Putu Diah; Pratiwi, A.A. Manik (Jurnal Kepariwisataan dan Hospitalitas; Vol 5 No 1 (2021): Vol.5,No.1,2021DO - 10.24843/JKH.2021.v05.i01.p06, 2021)
Abstract                     The tourism industry is experiencing rapid development in Indonesia today. This is evident from the increasing number of tourism businesses established in almost all regions in Indonesia. This collection of tourism businesses is interrelated with each other in providing the needs of tourists to feel comfortable to live in that place. Tourism businesses include tourist attractions, tourism areas, tourism transportation services, travel services, food and beverage services, accommodation, organizing entertainment and recreational activities, SPA, etc. SPA has become one of the fastest growing tourism businesses today, because SPA is included in health tourism activities. Star hotels contribute to improving the operation of SPA tourism businesses through the provision of this business in business administration services at hotels. The ethics services of female SPA workers in star-rated hotels in the Traditional Village of Seminyak must be applied in the operational work of the hotel. With the existence of good service ethics, tourists who enjoy this service will feel satisfied so that it will not close the possibility of having a positive impact on other business sectors in the hotel.               This research uses descriptive method, which is a method used to obtain an overview of the research objectives. To analyze tourists responses/perceptions of the ethics of female workers' services SPA used a Likert Scale, by distributing questionnaires to tourists who were made respondents.               The results of the research model on the application of the ethics of female SPA service workers to star hotels in Seminyak Traditional Village consists of 3 stages, the first stage is the ethics of guest service before treatment in terms of tangible or physical aspects and reliability or reliability. The second stage is the ethics of guest service during treatment in terms of assurance or assurance and empathy or attention. The third stage is responsiveness or responsiveness.   Keywords: Ethics, Services, Women Workers, SPA